Seventy years of changes in riverine woodland cover: Responses to elephants and human legacy effects in Gonarezhou National Park, Zimbabwe - Hawker, Johanna (Department of Biological Sciences, 2023)
As global biodiversity decreases, the importance of protected areas for protecting biodiversity and ecosystem complexity, is rising. Increasing development and land use change means that protected areas must restrict species to their boundaries to avoid human-wildlife conflict. Populations of species therefore no longer disperse, and overpopulation can occur. In southern African savanna systems, large populations of savanna elephant (Loxodonta africana) are transforming woodland and reducing vegetation diversity. While historically large, the elephant population in Gonarezhou National Park in Zimbabwe has grown at >5% annually since 1992, and densities currently exceed 2 elephants km-2 . Over the last 70 years, riverine woodland vegetation has undergone substantial changes. While initially it might be compelling to hold elephants responsible, Gonarezhou National Park has a complex natural and socio-ecological history to consider. Before proclamation in 1974, areas supporting woody riverine vegetation along Gonarezhou National Park's biggest river, the Runde, were widely cultivated. Some riverine vegetation was also cleared in the late 1950s to prevent the spread of tsetse fly (a vector for African Sleeping Sickness). This study makes use of aerial photography and satellite imagery of the Runde River, and its confluence with the Save River, covering the period 1948 to 2018. Using supervised classification techniques, imagery was analysed to identify vegetation types and provide an estimation of riverine woodland cover. Further analyses were conducted to assess characteristics and possible drivers of change. Percentage cover of woody riverine vegetation along the Runde River, covering a total area of 60.2 km2 , varied greatly over time, rising initially from 14% cover in 1948 to 40% cover in 2005 with cessation of cultivation and clearing for tsetse fly after the park was proclaimed. It then decreased by 20% between 2005 and 2018 most likely due to high populations of elephants and severe droughts. Confirmation that elephants have caused a decrease in woody cover of riverine woodland within Gonarezhou National Park was gained from comparing a plot inside the park boundary with an equivalent plot outside the park boundary that has supported a lower density of elephants. Woodland cover in these plots showed a significant reduction inside the park boundary suggesting elephants have driven this decline. The area of riverine woodland which was previously cultivated (3.3 km2 along the Runde River) supported between 1% and 12% less riverine woodland cover than areas which were not cultivated for each year of assessment, but the differences were not significant. The area of riverine woodland cleared for tsetse fly control (0.4 km2 along the Runde River) in the late 1950s supported between 8% and 25% less riverine woodland cover than uncleared areas in each year. Although some recovery is evident, there is a significant long-term influence of tsetse clearing on riverine woodland vegetation cover in Gonarezhou National Park. Elephant impacts are expected to decline with distance from permanent water. However, examination of changes in woody cover along a seasonal river, offering a potential refugium, yielded variable results. By 2018 a decrease in woodland cover adjacent to the permanent water source of the Runde River was apparent, suggesting that riverine woody vegetation near permanent water is most affected by elephant damage. A hypothesis that elephant impact on woodlands is lessened where there is a concentration of alternative food sources, especially hygrophilous grassland and Faidherbia albida pods, was examined. Woody cover along the Runde at its junction with the Save, which has substantial alternative forage, was compared to upstream areas without such alternatives. In 2018 a decrease in woody cover is shown with distance from alternative food sources, suggesting elephants use woodland more intensively when alternative forage is unavailable. The probable influence of drought and flooding events on reducing alternative forage and woody cover, requires further consideration. Woody cover is a crude index of change as it does not account for structure or composition of woodland below the canopy. As a result, if a significant change is detected, we can be quite confident that the change has occurred. However, if there is no significant change, this does not necessarily mean that changes have not taken place, they simply may not be detected by such a crude measure. Analysis of woodland cover serves as a starting point. Time and resource limitations meant that structure and composition could not be considered in this study. However, such measures would increase the accuracy of analysis in future studies. Overall, this study demonstrates the importance of considering all possible influences on vegetation change. Strong evidence was provided that elephants impact upon woody vegetation change over time. However, the longer-term influences of cultivation and tsetse clearing and, availability of refugia and alternative forage cannot be disregarded. An assiduous approach is required lest we falsely attribute blame to elephants alone, the management consequences of which are profound.